PENERAPAN NILAI KEJUJURAN DALAM PERISTIWA ISRA MI’RAJ DAN BURUNG HUDHUD - Rizki Aminullah (AT-TAISIR: Journal of Indonesian Tafsir Studies, 2021)
Honesty is one of the commendable qualities that must be possessed by everyone, both believers and non-believers. In everyday life, this honest nature must be reflected in every activity. It often happens that someone's honesty is greatly influenced by the situation at hand. If the situation is favorable, then do not hesitate to tell the truth, but on the contrary if the situation is not favorable, then it is likely that honesty is hidden. This paper examines the application of the value of honesty contained in the Qur'an. Several events in the Qur'an write about the application of the value of honesty, including the Isra Mi'raj incident and the Hudhud bird incident. This paper will describe the conditions in which the application of the value of honesty in the isra mi'raj and hudhud bird events has a background and consequences in its implementation. This is expected to be a lesson for Muslims in particular, in applying the value of honesty in everyday life.